A Barcode-Based Medical Asset Management System with Integrated Monitoring in Hospitals - Zalina Fatima Azzahra; Sinung Suakanto (JUSIFO : Jurnal Sistem Informasi, 2025)
This study proposes a barcode-based medical asset management system designed to address persistent challenges in hospital asset tracking, integration, and condition monitoring. Using the Design Science Research (DSR) methodology, the system was developed and implemented in Bhayangkara Sartika Asih Hospital, Indonesia. Key features include centralized data entry, QR code generation for unique asset identification, advanced search filters, and a real-time dashboard for visualizing asset conditions and distribution. Black box and usability testing involving 10 users demonstrated a 100% success rate in functional execution and high user acceptance, with 87.5% of respondents expressing satisfaction with the system’s usability and effectiveness. This system enhances traceability, reduces redundancy, and supports data-driven decision-making in asset procurement and maintenance. The study also highlights the potential for broader adoption across Indonesian hospitals, with future integration of IoT components recommended to enable automated real-time asset condition updates. The proposed system contributes to the digital transformation of healthcare infrastructure in line with national health priorities.